Performance Analysis of Co-Operative Beacon Sensing Strategies for Spatially Random Cognitive Users - Kusaladharma, Sachitha; Tellambura, Chintha (IEEE transactions on cognitive communications and networking, 2017)
Primary user (PU) beacons must be detected by cognitive users (CUs) to access spectrum holes, and misdetection results in interference on PUs. To alleviate this problem, sensing results of spatially separated CUs can be combined to make a final decision. In this paper, we analyze several such co-operative beacon sensing (CBS) strategies given spatial randomness of CU and PU nodes, which is modeled via independent homogeneous Poisson point processes. We consider two cases of beacon emitter placement: 1) at PU-transmitters and 2) at PU-receivers. We analyze three separate local beacon detection schemes and propose five CBS schemes. They require the sharing of CU results via a control channel subject to Rayleigh fading and path loss, and making a final decision via the OR rule. By using stochastic geometry, we derive both the misdetection probability, the false alarm probability, and the primary outage and show that impressive gains are achievable. For example, with PU-receiver beacons, CBS reduces misdetection by a factor of 104. In contrast, with PU-transmitter beacons, the reduction diminishes with the increased cell radii, but there exists an optimum cooperation radius.